2020
DOI: 10.1111/jssr.12699
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mortality Rates between Haredi and Non‐Haredi Jews in Israel in the Context of Social Characteristics

Abstract: Research indicates that mortality rates are lower among the religious. Israeli ultra‐orthodox Jews, called Haredim, have characteristics distinguishing them from the rest of the Jewish population in Israel. These include lower socioeconomic status, higher fertility rates and rates of young marriage, and isolation from the general population. Our retrospective cohort study aims to determine the difference in mortality rates between Haredi and non‐Haredi Jews in Israel. We collected data on sociodemographic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…On certain topics, their lack of knowledge could be a result of taboos, mainly when the topic relates to “immodest organs” (Zalcberg 2009 ). For instance, ultra-Orthodox women are significantly less aware of breast cancer and early detection tests than are non-ultra-Orthodox women, which consequently results in lower rates of testing for ultra-Orthodox women (Pinchas‐Mizrachi et al 2020 ). Further, the rate of people who waive medical treatments in ultra-Orthodox society is higher than the rate amongst the majority society; this discrepancy is also due to income gaps between the two groups (Kasir et al 2017 ).…”
Section: The Ultra-orthodox Society In Israel: Background and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On certain topics, their lack of knowledge could be a result of taboos, mainly when the topic relates to “immodest organs” (Zalcberg 2009 ). For instance, ultra-Orthodox women are significantly less aware of breast cancer and early detection tests than are non-ultra-Orthodox women, which consequently results in lower rates of testing for ultra-Orthodox women (Pinchas‐Mizrachi et al 2020 ). Further, the rate of people who waive medical treatments in ultra-Orthodox society is higher than the rate amongst the majority society; this discrepancy is also due to income gaps between the two groups (Kasir et al 2017 ).…”
Section: The Ultra-orthodox Society In Israel: Background and Characteristicsmentioning
confidence: 99%
“…While the ultra-Orthodox population demonstrates a low level of health-promoting behaviors, its members are characterized with aspects known to be health-promoting, such as high social capital, religious rituals and practices, and a faith-based worldview (Chernichovsky and Sharony 2015 ). In addition, a recent study shows that the ultra-Orthodox have lower mortality than other Israelis despite lower socioeconomic status (Pinchas‐Mizrachi et al 2020 ). In light of this, questions regarding the circumstances that led to the high morbidity rates of COVID-19 among the ultra-Orthodox population and regarding the place of its health-promoting aspects in this context become more acute.…”
Section: The Ultra-orthodox Society In Israel: Background and Characteristicsmentioning
confidence: 99%
“…Still, the general health level of the Haredi population is considered high relative to the general population (Chernichovsky & Sharony, 2015 ). In general, it has longer life expectancy than other Israelis (Pinchas-Mizrachi et al, 2020 ) thanks to aspects embedded in the religion known to promote health, such as religious rituals and practices, a faith-based worldview, and particularly high social capital (Chernichovsky & Sharony, 2015 ). Many studies refer specifically to elements of social capital embedded in the religious community that promote health behaviors and improve health among believers while emphasizing the role of clergy, religious institutions, religious affiliations, inter-communal welfare, and networking, and their importance in providing privileged access to resources (Milstein et al, 2020 ; Satariano, 2020 ; Shapiro & Sharony, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This group is characterized by unhealthy behavior which includes low compliance with mammography screening (Pinchas-Mizrachi et al 2021a , 2021b ), higher obesity rates (Leiter et al 2020 ), and low usage of dental care services (Lazarus et al 2015 ). An additional consideration in the evaluation of health behavior among Haredi Jews should relate to the fact that previous studies have found that the Haredi community tends to shy away from self-exposure, or revealing one’s vulnerabilities (Band-Winterstein and Freund 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier studies have indeed found better health outcomes among the Haredi community in comparison to the non-Haredi Jewish community. These outcomes may be explained by the social capital prevalent among the members of the community (Pinchas-Mizrachi et al 2021a , 2021b ).…”
Section: Introductionmentioning
confidence: 99%